The Hermeunetic Concept of The Qur'ān Muhammad Shaḥrūr - Nawal Nur Arafah (Eduvest - Journal of Universal Studies, 2023)
The purpose of this paper is to elaborate on the developmentof the qur'ān's pentak wilan transformation from a literal (textual) approach to a contextual approach by the hermeneutic method initiated by the contemporary Muslim intellectuals of Shaḥrūr. The idea of Shaḥrūr can beused as a method of interpreting the Qur'ān in this era of globalization so that Muslims can continue to adapt to the times. This paper is written using a library research model, because the objects of study are things related to various literature literature. This research uses a philosophical-hermeneutical method that is included in the qualitative approach, which intends to understand phenomena about the object of study, with the method of description in the form of words and language (narrative). Shaḥrūr introduced a linguistic approach called al-manhaj al-tarīkhī. Initially, he combined the linguistic methods of Abū 'Alī al-Fārisī, Ibn Jinnī, and 'Abd al-Qadīr al-Jurjāni. But eventually Shaḥrūr concluded the absence of synonyms in Arabic and Shaḥrūr also made Mu'jam Maqāyis al-Lughah by Ibn Fāris, one of the adherents of the absence of synonymity, his mandatory reference. It was this absence of synonymity that later became one of the principles of the Shaḥrūr method of interpretation. In addition to the synonmatic denial in the hermentic method Shaḥrūr is identical about the theory of hudud or limit.